Electrochemical exfoliation of a graphite electrode in 1-ethyl-3-methylimidazolium chloride-[EMIM]+Cl−–AlCl3 ionic liquid and its electrocatalytic application. Issue 6 (22nd February 2021) - Saravanan, Gengan; Sanjay, Sankaranarayanan; Gnanamuthu, R. M.; Sankararao, Mutyala
Abstract : An eco-friendly and economically viable electrochemical exfoliation method has the potential to produce few-layer graphene as a support for a dendritic Pt nanoparticle modified electrode for better non-enzymatic electrooxidation of glucose. Abstract : The electrochemical exfoliation of graphite using 1-ethyl-3-methylimidazolium chloride-[EMIM]Cl–AlCl3 ionic liquid (IL) has been anticipated to be an environmentally benign and economically viable graphene production technique based on the intercalation of AlCl4 − ions into a graphite anode in an IL mixture. An equimolar mixture of the two solids AlCl3 − and EMIMCl − becomes a liquid at room temperature via the acid–base reaction to form AlCl4 − and EMIM + ions. This liquid is not only an electrolyte, but also a source of electroactive species for intercalation into graphite. The crystallographic properties of graphite and physicochemical properties of the IL enable better intercalation of AlCl4 − (2.95 Å) into the graphite layer (lattice distance 3.3 Å). The results clearly demonstrate that graphene is produced within the graphite anode in AlCl3 –EMIM + Cl − . The IL is significantly important in terms of its cost efficiency, wide electrochemical window, and high exfoliation performance for the production of graphene. The as-prepared few-layer graphene was drop-casted on a pre-polished glassy carbon electrode (GCE), followed by the electrodeposition of Pt dendritic nanoparticles, for application in the electrooxidation of glucose.